PENGARUH BERBAGAI MEDIA TUMBUH TERHADAP KANDUNGAN AIR, PROTEIN DAN LEMAK MAGGOT YANG DIHASILKANSEBAGAI PAKAN - Muhammad Aldi, Farida Fathul , Syahrio Tantalo dan Erwanto (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2018)
This research aims to know the influence of various media to grow toward moisture content, protein and fat maggot as feed and knowing the kind of media to grow the best influence on moisture content, protein and fat maggot as feed. This research was conducted in April 2017 until May 2017 in the Laboratory of Airy, Faculty of Agriculture, University of Lampung. Proksimat analysis was performed in the Laboratory of Nutrition and Food for Livestock, Department of Animal Husbandry, Faculty of agriculture, University of Lampung. This study uses treatment of various places growing i.e. R1 (tofu waste), R2 (for cake oil palm), R3 (fish waste), and R4 (chicken blood). The experimental design was used, namely a complete Random Design (RAL) consists of four treatments and five replicates. Variables in this study i.e., moisture, protein, and fat maggot generated. Results of the study showed that treatment effect was not real (P>0.05) to moisture content, but very real effect (P<0.01) to the fat and protein content of maggot. The best media to grow maggot found in media of the chicken blood to the protein content and the media to grow of the fat content was fish waste. Keywords: maggot, media to grow, nutrition maggot